Клинические практические рекомендации IPNA по диагностике и лечению детей со стероид-резистентным нефротическим синдромом - Trautmann, Agnes; Vivarelli, Marina; Samuel, Susan; Gipson, Debbie; Sinha, Aditi; Schaefer, Franz; Hui, Ng Kar; Boyer, Olivia; Saleem, Moin A.; Feltran, Luciana; Müller-Deile, Janina; Becker, Jan Ulrich; et al. (Нефрология и диализ, 2021)
Idiopathic nephrotic syndrome newly affects 1-3 per 100,000 children per year. Approximately 85% of cases show complete remission of proteinuria following glucocorticoid treatment. Patients who do not achieve complete remission within 4-6 weeks of glucocorticoid treatment have steroid-resistant nephrotic syndrome (SRNS). In 10-30% of steroid resistant patients, mutations in podocyte-associated genes can be detected, whereas an undefined circulating factor of immune origin is assumed in the remaining ones. Diagnosis and management of SRNS is a great challenge due to its heterogeneous etiology, frequent lack of remission by further immunosuppressive treatment, and severe complications including the development of end-stage kidney disease and recurrence after renal transplantation. A team of experts including pediatric nephrologists and renal geneticists from the International Pediatric Nephrology Association (IPNA), a renal pathologist, and an adult nephrologist have now developed comprehensive clinical practice recommendations on the diagnosis and management of SRNS in children. The team performed a systematic literature review on 9 clinically relevant PICO (Patient or Population covered, Intervention, Comparator, Outcome) questions, formulated recommendations and formally graded them at a consensus meeting, with input from patient representatives and a dietician acting as external advisors and a voting panel of pediatric nephrologists. Research recommendations are also given.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Children; Chronic kidney disease; Genetics; Immunosuppressive treatment; Outcome; Pediatrics; Steroid-resistant nephrotic syndrome